Study of the career motivators of accounting students in UUM - Selamat, Mohamad Hisyam; Syed Ismail, Syed Soffian; Engku Ali, Engku Ismail (Universiti Utara Malaysia, 2001)
This study profiling the career drivers of final-year accounting students at Universiti Utara Malaysia. Specifically, the study identifies what an accounting students is looking for in a career. Comparative examinations of the career drivers are performed by the gender and race. The career driver scores of accounting and non-accounting students are also compared. The results suggest the presence of statistically significant differences between male and female accounting students in the career drivers of power/influence and security. When bumiputra and non-bumiputra setting is used as a basis of comparison, there are statistically significant differences among the accounting students in the areas of status and search for meaning. Accounting and non-accounting students exhibit differences in the career drivers of material rewards, power/influence, search for meaning, expertise, autonomy and security at a statistically significant level of p<0.05. Implications and suggestions for future research are discussed.